Using Educational Online Resources for the Formation of Professional Communicative Competence of Future Teachers of French - Н. В. Майєр (Іноземні мови, 2013)
The article considers the concept of professional competence of future teachers of foreign languages, describes its components. The author identifies criteria and analyzes educational Internet resources to be used by future teachers of French in order to develop their professional communicative competence in French.